Analisis 7S McKinsey PT. Hasil Rotibua Abadi Untuk Perbaikan Organisasi - Rydho Jalu Nuringtyas (Jurnal Bisnis dan Keuangan, 2020)
This study aims to identify and find solutions to delay construction work happening on the SCE project. The SCE project is a school building construction project. The background of this study is due to indications of delay with a difference of 25% between the schedule plan and the reality in the ground. The factors that cause the delay must be well identified so that a larger delay can be avoided and can provide solutions to these problems. From the results of Fishbone analysis and AHP, 11 factors were found to influence the delay in SCE project.